Question
upstudy study bank question image url

\( q(x)=2+x-2 x^{2}-x^{3}, x \in \mathbb{R} \), is a cubic function. (a) Find each of the following: (i) \( q(-1) \) (ii) \( q^{\prime}(x) \) (iii) \( q^{\prime}(-1) \) b) \( y=q(x), x \in \mathbb{R} \), is a graph of \( q(x) \). (i) Show that \( (1,0) \) is a point on the graph of \( q(x) \). (ii) Find the slope of the tangent to \( y=q(x) \) at the point \( (1,0) \). (iii) Hence, find the equation of the tangent to \( y=q(x) \) at \( (1,0) \). Give your answer in the form \( a x+b y+c=0 \). [Hint: use \( y-y_{1}=m\left(x-x_{1}\right) \) ]

Ask by Wade Maxwell. in Ireland
Feb 03,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

**Simplified Answers:** a) i) \( q(-1) = 0 \) ii) \( q^{\prime}(x) = -3x^{2} - 4x + 1 \) iii) \( q^{\prime}(-1) = 2 \) b) i) \( (1, 0) \) is a point on the graph of \( q(x) \). ii) The slope of the tangent at \( (1, 0) \) is \( -6 \). iii) The equation of the tangent at \( (1, 0) \) is \( 6x + y - 6 = 0 \).

Solution

Let's analyze the cubic function \( q(x) = 2 + x - 2x^{2} - x^{3} \) and address each part of the problem step by step. --- ## **a) Calculations Involving \( q(x) \)** ### **i) Find \( q(-1) \)** To find \( q(-1) \), substitute \( x = -1 \) into the function: \[ \begin{align*} q(-1) &= 2 + (-1) - 2(-1)^{2} - (-1)^{3} \\ &= 2 - 1 - 2(1) - (-1) \\ &= 2 - 1 - 2 + 1 \\ &= (2 - 1) + (-2 + 1) \\ &= 1 - 1 \\ &= 0 \end{align*} \] **Answer:** \( q(-1) = 0 \) --- ### **ii) Find \( q^{\prime}(x) \)** To find the derivative \( q^{\prime}(x) \), differentiate \( q(x) \) with respect to \( x \): \[ \begin{align*} q(x) &= 2 + x - 2x^{2} - x^{3} \\ q^{\prime}(x) &= \frac{d}{dx}(2) + \frac{d}{dx}(x) - \frac{d}{dx}(2x^{2}) - \frac{d}{dx}(x^{3}) \\ &= 0 + 1 - 4x - 3x^{2} \\ &= -3x^{2} - 4x + 1 \end{align*} \] **Answer:** \( q^{\prime}(x) = -3x^{2} - 4x + 1 \) --- ### **iii) Find \( q^{\prime}(-1) \)** Using the derivative found in part (ii), substitute \( x = -1 \): \[ \begin{align*} q^{\prime}(-1) &= -3(-1)^{2} - 4(-1) + 1 \\ &= -3(1) + 4 + 1 \\ &= -3 + 4 + 1 \\ &= 2 \end{align*} \] **Answer:** \( q^{\prime}(-1) = 2 \) --- ## **b) Graph Analysis of \( y = q(x) \)** ### **i) Show that \( (1, 0) \) is a Point on the Graph of \( q(x) \)** To verify that \( (1, 0) \) lies on the graph of \( q(x) \), substitute \( x = 1 \) into \( q(x) \) and check if \( y = 0 \). \[ \begin{align*} q(1) &= 2 + (1) - 2(1)^{2} - (1)^{3} \\ &= 2 + 1 - 2(1) - 1 \\ &= 2 + 1 - 2 - 1 \\ &= (2 + 1) + (-2 -1) \\ &= 3 - 3 \\ &= 0 \end{align*} \] Since \( q(1) = 0 \), the point \( (1, 0) \) lies on the graph of \( q(x) \). **Answer:** \( (1, 0) \) is a point on the graph of \( q(x) \). --- ### **ii) Find the Slope of the Tangent to \( y = q(x) \) at \( (1, 0) \)** The slope of the tangent at a point \( x = a \) is given by the derivative \( q^{\prime}(a) \). From part **a(ii)**, we have: \[ q^{\prime}(x) = -3x^{2} - 4x + 1 \] Substitute \( x = 1 \): \[ \begin{align*} q^{\prime}(1) &= -3(1)^{2} - 4(1) + 1 \\ &= -3 - 4 + 1 \\ &= -6 \end{align*} \] **Answer:** The slope of the tangent at \( (1, 0) \) is \( m = -6 \). --- ### **iii) Find the Equation of the Tangent to \( y = q(x) \) at \( (1, 0) \)** We can use the point-slope form of a line: \[ y - y_{1} = m(x - x_{1}) \] Where: - \( m \) is the slope - \( (x_{1}, y_{1}) \) is the point on the line Given: - \( m = -6 \) - \( (x_{1}, y_{1}) = (1, 0) \) Substitute these values: \[ \begin{align*} y - 0 &= -6(x - 1) \\ y &= -6x + 6 \end{align*} \] To express this in the form \( a x + b y + c = 0 \), rearrange the equation: \[ \begin{align*} y &= -6x + 6 \\ 6x + y - 6 &= 0 \end{align*} \] **Answer:** An equation for the tangent is \( 6x + y - 6 = 0 \). ---

Reviewed and approved by the UpStudy tutoring team

error msg
Explain
Simplify this solution

Bonus Knowledge

To solve your cubic function challenge, let's dive into each part step by step! First, calculating \( q(-1) \): Substituting \(-1\) into the function gives: \[ q(-1) = 2 + (-1) - 2(-1)^2 - (-1)^3 = 2 - 1 - 2 + 1 = 0 \] Now, let's find the derivative \( q^{\prime}(x) \): To differentiate the function, we get: \[ q^{\prime}(x) = 0 + 1 - 4x - 3x^2 = 1 - 4x - 3x^2 \] Next, we evaluate \( q^{\prime}(-1) \): Substituting \(-1\) into the derivative gives: \[ q^{\prime}(-1) = 1 - 4(-1) - 3(-1)^2 = 1 + 4 - 3 = 2 \] Now, moving onto part (b), we want to show that \((1,0)\) is a point on the graph of \( q(x) \): Calculating: \[ q(1) = 2 + 1 - 2(1)^2 - (1)^3 = 2 + 1 - 2 - 1 = 0 \] Thus, the point \((1,0)\) is indeed on the graph! To find the slope of the tangent at \((1,0)\): We already found that \( q^{\prime}(1) \) is: \[ q^{\prime}(1) = 1 - 4(1) - 3(1)^2 = 1 - 4 - 3 = -6 \] Lastly, we need the equation of the tangent line in the form \( ax + by + c = 0 \): Using the point-slope form \( y - y_1 = m(x - x_1) \): \[ y - 0 = -6(x - 1) \] Simplifying gives: \[ y = -6x + 6 \\ 6x + y - 6 = 0 \] Thus, the equation of the tangent line is \( 6x + y - 6 = 0 \). Enjoy your exploration of cubic functions!

Related Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy